Ultramicrosensors based on transition metal hexacyanoferrates for scanning electrochemical microscopy - Komkova, Maria A.; Holzinger, Angelika; Hartmann, Andreas; Khokhlov, Alexei R.; Kranz, Christine; Karyakin, Arkady A.; Voronin, Oleg G. (Beilstein Journal of Nanotechnology, 2013)
We report here a way for improving the stability of ultramicroelectrodes (UME) based on hexacyanoferrate-modified metals for the detection of hydrogen peroxide. The most stable sensors were obtained by electrochemical deposition of six layers of hexacyanoferrates (HCF), more specifically, an alternating pattern of three layers of Prussian Blue and three layers of Ni–HCF. The microelectrodes modified with mixed layers were continuously monitored in 1 mM hydrogen peroxide and proved to be stable for more than 5 h under these conditions. The mixed layer microelectrodes exhibited a stability which is five times as high as the stability of conventional Prussian Blue-modified UMEs. The sensitivity of the mixed layer sensor was 0.32 A·M−1·cm−2, and the detection limit was 10 µM. The mixed layer-based UMEs were used as sensors in scanning electrochemical microscopy (SECM) experiments for imaging of hydrogen peroxide evolution.
Keywords: energy related; hydrogen peroxide; nanomaterials; nickel hexacyanoferrate; Prussian Blue; scanning electrochemical microscopy; ultramicroelectrodes